FAKTOR-FAKTOR PENYEBAB TERJADINYA TINDAK PIDANA KORUPSI OLEH KEPALA DAERAH (GUBERNUR, BUPATI/WALIKOTA) DI INDONESIA - Mohamad Djatmiko (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2024)
Corruption in Indonesia remains significantly high and has not yet to be effectively addressed. This is evident from the Corruption Perception Index released by Transparency International, an organization that measures corruption levels in 180 countries worldwide. In 2024, Indonesia ranked 65th worst out of 179 countries in term of corruption its corruption levels. Among the cases handled by The Corruption Eradication Commission (KPK) and other law enforcement agencies are those involving regional heads (Governor and Deputy, Regent and Deputy, as well as Mayor and Deputy), wich are notably prominent both in quality and quantity. The factors contributing to corruption by regional heads have been analysed using the crime occurance model by The National Crime Bureau of Justice Assistance, US Department of Justice (Awaluddin Djamin, 2015). This model suggests that crime occur due to the convergence of intention, capability, opportunity, and target. Applied to corruption cases involving regional leders, it can be outlined as follows. The intention arises due to the substantial political costs that candidates for regional heads positions incur along with their running mates. Thesecandidate are aware of the high costs involved, cost that cannot be recouped through legitimate means during their five-year tenure. Consequently, they seek to recover these expenses through illegal transactions categiorized as corruption offenses. The high political costs thus reprenset the rootcause behind the occurrence of corruption offenses by regional leaders, while other factors such as the capability to commit corruption, the opportunity todo so and identifiable targets serve as contributing factor. Therefore, efforts are needed forboth prevention and mitigation, addressing about primary factors and additional contributing factors to corruption offenses by regional leaders.